Cometale - an interactive showcase of comets - Xue, Fuguo (Nanyang Technological University, 2023)
Cometale is an interactive installation that explores the relationship between comets and our world through the lens of Artificial Intelligence (AI) painting technology. Inspired by "Divination by Astrological and Meteorological Phenomena," a Chinese silk book that demonstrates the divination practice using astrology and meteorology, the installation consists of a scroll-shape projection screen displaying a series of AI-generated synthetic comet animations, creating a unique and personalized experience for each participant.